Correlation Studies Among Line Operation Parameters Between CPE and MSAN - Raden Sumarto, Raden Mohamad Syaifullah; Md Mustam, Saizalmursidi; Che Seman, Fauziahanim (Evolution in Electrical and Electronic Engineering, 2021)
The purpose of this project is to studies the correlation between Line Operation Parameters (LOPs) between Customer Premises Equipment (CPE) and Multi-Service Access Node (MSAN). As focusing on CPE sites, the project also is developing data acquisition and extraction on the CPE device, which can observe various network parameters for preventing a total breakdown in the network system. Hence, through the data collection, the statistical performance of CPE devices based on the network parameters such as actual line rate, attainable rate, line and signal attenuation and Signal-to-Noise Ratio (SNR) margin were evaluated. This project focuses on a Very high-speed Digital Subscriber Line 2 (VDSL2) access network, in which the copper cable length varies between several distances, 100 m, 300 m, 500 m, 700 m and 1000 m. The copper cable is a twisted-pair type that bundles ten pairs, and from the ten pairs twisted-pair, only six-port from MSAN is used and connected to the load CPE, Huawei HG655m modem. A web scraping technique using Python programming script is developed to extract and collect LOP parameters and statistical performance data available on Graphical User Interface (GUI) for Huawei HG655m modem. The extracted and collected data is saved in comma-delimited (.csv) file format. The Huawei HG655m modem can achieve maximum data rate speed at 100 m of copper cable length with 100009 kbps and 41786 kbps downstream and upstream. At 300 m, the data rate speed drop by 7.7% and 8.8% for downstream and upstream. 14.1% and 22.5% of data rate speed drop downstream and upstream at 500 m copper cable length. As the distance between MSAN and CPE reaching 700 m and 1000 m, the data rate speed drop drastically with 37.% and 55.6% for downstream, while 51.5% and 77.7% for upstream.